The Chaos-Based Whale Optimization Algorithms Global Optimization - Ali Fuat Boz; Durmuş Karayel; Murat Erhan Cimen; Zeynep Garip (Chaos theory and applications, 2019)
Whale optimization algorithm (WOA) is one of the methods used effectively and efficiently to solve optimization problems in various fields. In the study, 5 different discrete chaotic maps were used in the aim of increasing the efficacy and efficiency of the WOA algorithm. CBWOA 1, CBWOA 2, CBWOA 3 and CBWOA 4 algorithms based on chaotic maps and whale optimization algorithm have been proposed for global optimization. In order to adjust the parameters contained in the WOA, random number sequences from Tinkerbell, Sine, Logistic, Tent and Henon chaotic maps were used. In order to test the accuracy of the developed algorithms and do the performance analysis, six different unimodal and multimodal benchmark functions were used. According to the simulation results, all the chaotic maps used in the study significantly improved the performance of the WOA algorithm.